Caregiver-Implemented Digital Activity Schedules With Virtual Coaching. Issue 2 (March 2023) - Aguilar, Juliana; Peck, Sara; Mattson, Stephanie L.; Reinert, Kassidy S.; Higbee, Thomas S.; Lindgren, Nicholas A.; Osos, Jessica A.
During the COVID-19 pandemic, many insurance companies approved the funding of telehealth-based behavior analytic services for both training and direct-care purposes. Activity schedules are a simple and effective intervention that can be used in the home environment to improve independence for children with ASD. Recent efforts have shifted the format of activity schedules from paper-based schedules to digital platforms that make the schedules more portable and provide easier access for both the caregiver and the Board Certified Behavior Analyst (BCBA). Google Slides ® is a readily available web-based platform that has been used to design and deliver behavior analytic instruction during the COVID-19 pandemic. A non-concurrent multiple baseline design across three child-caregiver dyads was used to evaluate the effectiveness of a caregiver-implemented digital activity schedule intervention on the independent play behaviors of children with ASD. The activity schedule was created and shared on the Google Slides ® platform and caregivers received bug-in-ear (BIE) coaching from practitioners to implement the intervention. Regardless of some minor treatment implementation difficulties attributed to the remote service delivery and the digital format, the digital platform and coaching intervention were effective in increasing independent schedule following with minimal training on the part of the caregiver. We hope that the results of this study provide BCBAs with additional guidance on effective interventions and procedures for remote service delivery.